STUDENTS' PERCEPTION OF ADDITIONAL LEARNING IN IMPROVING OFFICIAL TEST SCORES - Lubis, Mutia Zahra Mikayla; Ramadhan, Muhammad Faiz; Nasution, Faras Hilal; Tarigan, Roffi Kabanta; Tarigan, Aldo Rasmana; Saragih, Risna Mira Bella (FKIP Universitas Al Washliyah Medan, 2026)
This study aims to analyze students' perception of additional learning in order to improve official test scores, especially in official class students at Al Azhar Superior High School Medan. The method used is a descriptive quantitative approach with a total sampling technique, involving all official class students as respondents. The research instrument is in the form of a Likert scale questionnaire which includes indicators of student perception of the material, learning methods, the role of teachers, and the effectiveness of additional learning on the understanding and results of the official test try-out. The results showed an average perception score of 4.14, which was classified as a positive category. The indicators with the highest scores were program sustainability (4.5) and clarity of teacher explanations (4.4), while indicators with relatively low scores were an increase in try out scores (3.8). These findings indicate that students consider additional learning beneficial, not only in improving material comprehension, but also in building confidence in facing official tests. In conclusion, students' positive perceptions of additional learning contribute significantly to their academic and affective readiness, so this program is worthy of being maintained and further developed to support students' success in official school selection